FRI0017 DIFFERENTIAL METHYLATION AS A PREDICTOR OF TOCILIZUMAB RESPONSE IN PATIENTS WITH RHEUMATOID ARTHRITIS. (June 2019) - Nair, Nisha; Plant, Darren; Isaacs, John; Morgan, Ann; Hyrich, Kimme; Barton, Anne; Wilson, Gerry
Abstract : Background: Tocilizumab (TCZ) is a biological disease-modifying antirheumatic drug that blocks IL-6 signalling and is effective in ameliorating disease activity in rheumatoid arthritis (RA). Despite this, approximately 50% of patients do not respond adequately to TCZ and some patients report adverse events. Considering there is growing evidence that DNA methylation is implicated in RA susceptibility and response to some biologics (1, 2), we investigated methylation patterns as a candidate biomarker for response to TCZ in RA. Objectives: To identify differential DNA methylation signatures in whole blood associated with TCZ response in patients with RA. Methods: Epigenome-wide DNA methylation patterns were measured using the Infinium EPIC BeadChip (Illumina) in whole blood-derived DNA samples from patients with RA. DNA was extracted from blood samples taken pre-treatment and following 3 months on therapy, and response was determined at 6 months using the Clinical Disease Activity Index (CDAI). Patients who had good response (n=10) or poor response (n=10) to TCZ by 6 months were selected. Samples from secondary poor responders (n=10) (patients who had an improvement of CDAI and were in remission at 3 months, followed by a worsening of CDAI at 6 months) were also analysed. Differentially methylated positions (DMPs) were identified using linear regression, adjusting for gender, age, cell composition, smoking status, and steroids use. Results: There were 20 DMPs significantly associated with response status at 6 months in the pre-treatment samples, and 21 DMPs associated with response in the 3 months samples (unadjusted P-value < 1.00E-06). Furthermore, there were 10 DMPs significantly associated with change in methylation between pre-treatment and 3 months samples in good responders, but there were no significant findings when comparing methylation between time points in poor responders or in secondary poor responders. One DMP, cg03121467, was significantly less methylated in good responders compared to poor responders in the pre-treatment samples (p=1.06E-06). Furthermore, methylation was lower in good compared with poor responders at 3 months (p=1.03E-07). This DMP is close to EPB41L4A, which is thought to have a role in β–catenin signalling. Conclusion: Whilst further analyses comparing sub-components of the CDAI with changes in methylation is ongoing, these preliminary results provide evidence that DNA methylation patterns may predict response to TCZ. Validation of these findings in other larger data sets is required. References: [1] Liu, Y., Aryee, M.J., Padyukov, L., Fallin, M.D., Hesselberg, E., Runarsson, A., Reinius, L., Acevedo, N., Taub, M., Ronninger, M., et al. (2013) Epigenome-wide association data implicate DNA methylation as an intermediary of genetic risk in rheumatoid arthritis. Nat. Biotechnol., 31, 142–147. [2] Plant, D., Webster, A., Nair, N., Oliver, J., Smith, S.L., Eyre, S., Hyrich, K.L., Wilson, A.G., Morgan, A.W., Isaacs, J.D., et al. (2016) Differential Methylation as a Biomarker of Response to Etanercept in Patients With Rheumatoid Arthritis. Arthritis Rheumatol. (Hoboken, N.J.), 68, 1353–60. Disclosure of Interests: Nisha Nair: None declared, Darren Plant: None declared, John Isaacs Grant/research support from: Pfizer, Grant/research support from: Pfizer, Consultant for: Abbvie, Pfizer, Roche, Galvani, Merck, Gilead, Eli Lilly, Amgen, Janssen, Celltrion, NAPP, Consultant for: Abbvie, Pfizer, Roche, Galvani, Merck, Gilead, Eli Lilly, Amgen, Janssen, Celltrion, NAPP, Speakers bureau: Abbvie, Pfizer, Eli Lilly, Speakers bureau: Abbvie, Pfizer, Eli Lilly, Ann Morgan: None declared, Kimme Hyrich Grant/research support from: Grants to institution: BMS, Pfizer, UCB, Anne Barton: None declared, Gerry Wilson: None declared